ECOLOGICAL GROUPING OF PLANT PHYTONEMATODES (American Journal of Pedagogical and Educational Research, 2023)
Mesathermal hygrophils are confined to floodplain forests (tugai) of river valleys. In irrigated farming, megathermal hygrophils can transition to a cultural area and cause enormous harm to agriculture. Mesathermal hygrophils include nematode species associated with biotopes with excessive moisture under moderate or cold temperature conditions.